Outcome mapping : building learning and reflection into development programs - Earl, Sarah, 1971- (desLibris. Books collection., 2001)
Outcome Mapping recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, Outcome Mapping debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in term.